Foreword from Handling Editor – 8th Edition - Dwiranti, Astari (ASEAN Journal of Community Engagement, 2020)
We are delighted to present the 8th edition of AJCE, published in December 2020. We have selected eleven of the best articles for this edition, consisted of six Research Articles, one Review Article, and four Case-Based Articles. These articles presented the valuable and interesting information with the broad ranges covering three sub-themes, i.e. education (Community engagement in COVID-19 responses, intellectual property rights, and technique to decrease depression level), Economy (participatory budget during the Covid-19 pandemic, and Empowering Botswana’s rural communities), and Health (Development-induced displacement on the Tribal community, Combating COVID-19 infodemic, Village fund accountability and gendering, stunting early detection, and Training program to support posbindu cadre knowledge). We want to express our thanks to the reviewers who gave inputs and contributions to improve the quality of the articles. Our greatest thanks are also due to Azhar Firdaus for helping us with the publication process and to the Directorate of Administration, Data, and Research Product and Innovation Management Universitas Indonesia (DADPPRI UI) for providing a journal development grant, and proofread assistance through ENAGO. Finally, we hope that readers enjoy the articles that we present in this edition.